Development and characterization of burger patty from coconut (Cocos nucifera) sapal. - Treyes, Nicolle Marie Japitana
Due to the growing awareness of the public on the possible harmful effects of too much consumption of processed red meat and high fat intake, there is an increased demand for the development of meat alternatives that can better complement a healthier diet. This study aimed to develop and characterize a meat-free burger patty made of sapal, a residue after milk extraction from grated mature coconut kerbel, in order to enhance the utilization of the sapal and minimize wastage from coconut production. The moisture content, crude ash, crude fat, crude fiber, crude protein, and carbohydrates pH, water activity, microbiological content of the sapal burger patty was analyzed and compared to a control beef burger patty. Sapal burger patty was analyzed to contain 49.90% moisture content, 2.74% crude ash, 30.19% crude fat, 2.53% crude fiber, 13.22% crude protein and 1.42% carbohydrates. T-test statistical analysis at 5% level of significance indicated that sapal burger patty has significantly higher moisture and fiber content and has significantly lower ash content compared to that of beef burger patty. Generally, the fat, protein, carbohydrate, pH, water activity, and total plate count of the sapal burger patty is not significantly different from that of the beef burger patty. The descriptive sensory analysis of the sapal burger patty presented that it has a brown outer color, a slight coconut aroma and flavor, the texture is tender and firm, and is juicy. Sixty-four percent (64%) of the respondents rated the product as ?like very much?. In general, this study presented a high general acceptability for the most preferred formulation of sapal burger patty that it has a good marketing potential especially since its quality is comfortable to that of the beef burger patty with a lower cost.